2020
DOI: 10.14295/holos.v20i4.12405
|View full text |Cite
|
Sign up to set email alerts
|

Decomposição foliar da serapilheira de dois sistemas agroflorestais no Cerrado Sul-Mato-Grossense

Abstract: Um dos indicadores importantes para um ecossistema é a serapilheira, pois ela fornece nutrientes e matéria orgânica que são essenciais para o funcionamento do ambiente. Assim sendo, o objetivo deste estudo foi avaliar a taxa de decomposição foliar da serapilheira e correlacioná-la com índices meteorológicos, em duas áreas com sistemas agroflorestais (SAF1) formado por diversas espécies de plantas e (SAF2) formado por Heveicultura e abacaxi, em uma região de Cerrado, no município de Pedro Gomes, MS. Para avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Em geral, a maior riqueza de grupos da macrofauna do solo esteve associada às áreas que apresentam uma espessa camada de serapilheira, servindo como habitat para uma grande diversidade de organismos (De Brito et al, 2016). Além de minimizar as variações de temperatura e umidade, acabam influenciando a dinâmica das reações químicas e os processos biológicos que ocorrem no solo (Bauer et al, 2018;Andrade;Amorim, 2018;Assis et al, 2020), mantendo em atividade a macrofauna edáfica.…”
Section: Resultsunclassified
“…Em geral, a maior riqueza de grupos da macrofauna do solo esteve associada às áreas que apresentam uma espessa camada de serapilheira, servindo como habitat para uma grande diversidade de organismos (De Brito et al, 2016). Além de minimizar as variações de temperatura e umidade, acabam influenciando a dinâmica das reações químicas e os processos biológicos que ocorrem no solo (Bauer et al, 2018;Andrade;Amorim, 2018;Assis et al, 2020), mantendo em atividade a macrofauna edáfica.…”
Section: Resultsunclassified
“…The lower decomposition rates observed in the T. grandiflorum and P. cupana areas can be attributed to lower moisture of the litter, related to high C:N ratio associated with high lignin concentrations (Walela et al, 2014;. Longer decomposition time is not an indication of malfunctioning agricultural systems, because the longer material remains on the soil surface, the greater its accumulation and surface coverage will be, providing soil protection (Assis et al, 2020) and providing long-term nutrients (Bai et al, 2022).…”
Section: Decomposition Of Leaf Littermentioning
confidence: 99%
“…Recent studies have indicated that organic matter decomposition and mineralization processes, at local level, are affected by the quality of the edaphic environment and microenvironment, i.e., by the interaction between the decomposer biota and soil factors such as moisture and temperature, whose combined effects depends on the biomass exposure time (SOUTO et al, 2013;PINTO et al, 2016;SOUZA et al, 2019;ASSIS et al, 2020). Thus, understanding the processes involved in decomposition and nutrient cycling and the factors that can affect the dynamics of this cycling is important for decision making related to the choice of appropriate management and species that will compose the system (SOUSA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%